Hearing Emerson, Lake, and Palmer Anew: Progressive Rock as “Music of Attractions” - Hung, Eric (Current Musicology, 2005)
Progressive rock is a loose label for music that combines some of the basic ingredients of early rock ‘n’ roll and elements of genres that are generally considered more prestigious, such as Western art music, jazz, and Indian classical music. After emerging in the late 1960s, progressive rock reached its peak in popularity in the early 1970s. Since the rise of punk in the mid 1970s, the genre has retreated to the college circuit, select clubs, and fringe festivals. Over the past quarter century, there have been two common stances on progressive rock. One builds upon rock critics’ longstanding and overwhelmingly negative view of the genre. For most critics, such as Dave Marsh and Lester Bangs, the most important element of rock is the rather ambiguous concept of “authenticity.” Theoretically, “authenticity” is connected with genuineness. A song is “authentic” when it is written (or at least arranged) by the performing musicians, and is about their lives and emotions. Although songwriting credits are easily conveyed, this notion of authenticity is not particularly useful in criticism. After all, how would a critic know whether or not the feelings expressed in a song are genuine? In practice, many critics track authenticity with more obvious qualities: a sense of rebelliousness, the inclusion of blues elements such as blues progressions and extended vocal melismas, and subtle inflections of the beat. Given these criteria, the negative critical reception of progressive rock-exemplified by the strongly worded Lester Bangs quote above-is hardly surprising. After all, progressive rock musicians diluted the influence of blues in rock music by incorporating elements of many other genres. They also took away the sexuality and rebelliousness often heard in rock’s hard-driving beat, replacing it with complex meters that are not suited to dancing.